Interannual variation in the East Asian summer monsoon-tropical Atlantic SST relationship modulated by the Interdecadal Pacific Oscillation - Hao Wang; Ziguang Li; Jianping Li; Xiaopei Lin; Xiao-Tong Zheng; Lei Fan; Yu Zhang (npj Climate and Atmospheric Science, 2023)
Abstract Tropical Atlantic (TA) SST variability can impact the East Asian summer monsoon (EASM). Here, we find that the interannual EASM–TA relationship exhibits an evident interdecadal variation modulated by the Interdecadal Pacific Oscillation (IPO). The EASM–TA interannual relationship is strong during the positive phase of the IPO (pIPO) but weak during the negative phase of the IPO (nIPO). The pIPO (nIPO)-related warm (cold) SST anomalies in the central tropical Pacific (CTP) intensify (weaken) the convection over the CTP. Therefore, a Matsuno–Gill response of the TA-induced CTP SST change is strong (weak) during the pIPO (nIPO) period. The strong Matsuno–Gill response excites an anomalous anticyclone over the western North Pacific (WNPAC), leading to a significantly positive EASM–TA relationship. However, the WNPAC is absent in the nIPO periods due to the weak Mastono–Gill response, suggesting an insignificant EASM–TA relationship. Understanding the IPO-modulated EASM–TA relationship helps better forecast EASM variability.